2019
DOI: 10.1016/j.ymthe.2019.04.020
|View full text |Cite
|
Sign up to set email alerts
|

Combined Antitumor Effects of Sorafenib and GPC3-CAR T Cells in Mouse Models of Hepatocellular Carcinoma

Abstract: Our previous study indicated that GPC3-targeted chimeric antigen receptor (CAR) T cell therapy has a high safety profile in patients with hepatocellular carcinoma (HCC). However, the response rate requires further improvement. Here, we analyzed the combined effect of GPC3-CAR T cells and sorafenib in both immunocompetent and immunodeficient mouse models of hepatocellular carcinoma. In immunocompetent mouse model, mouse CAR (mCAR) T cells induced regression of small tumors (approximately 130 mm 3 tumor volume) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
82
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 113 publications
(85 citation statements)
references
References 49 publications
(68 reference statements)
1
82
0
Order By: Relevance
“…Tumor angiogenesis is crucial for tumor growth and metastasis, thus blocking or inhibiting tumor angiogenesis could potentiate antitumor activities (42). In this study, we observed that Author Manuscript Published OnlineFirst on August 14, 2020; DOI: 10.1158/1078-0432.CCR-20-0777 CAR-T cells (43). Thus, the property of angiogenesis inhibition may enhance the antitumor activities of 7×21 CAR-T cells.…”
Section: Discussionmentioning
confidence: 74%
“…Tumor angiogenesis is crucial for tumor growth and metastasis, thus blocking or inhibiting tumor angiogenesis could potentiate antitumor activities (42). In this study, we observed that Author Manuscript Published OnlineFirst on August 14, 2020; DOI: 10.1158/1078-0432.CCR-20-0777 CAR-T cells (43). Thus, the property of angiogenesis inhibition may enhance the antitumor activities of 7×21 CAR-T cells.…”
Section: Discussionmentioning
confidence: 74%
“…Patients who met all screening criteria underwent leukapheresis to obtain peripheral blood mononuclear cells (PBMC) for the generation of autologous CAR-GPC3 T cells. As described previously (36), CAR-GPC3 T cells (product code Y035) consisted of a humanized anti-GPC3 single-chain variable fragment, CD8a hinge domain, CD8a transmembrane domain, CD28 intracellular domain, and CD3z intracellular signaling domain that were cloned into a lentiviral backbone (Fig. 1A).…”
Section: Clinical Trial Design and Patientsmentioning
confidence: 99%
“…Indeed, anti-GPC3 mAbs had good safety profiles in previous studies (34,35), although significant clinical benefit has yet to be established in phase II clinical trials. Recently, we demonstrated that GPC3targeted CAR T cells could eliminate GPC3 þ HCC cells in vitro and eradicate GPC3 þ HCC tumor xenografts in mice (36)(37)(38). Therefore, in the present prospective phase I studies, we explored the safety and potential efficacy of CAR-GPC3 T-cell therapy in adult Chinese patients with advanced GPC3 þ HCC.…”
Section: Introductionmentioning
confidence: 96%
“…Chimeric antigen receptor T cells (CAR-T): Recent studies of HCC tumor xenografts in mice and in vitro demonstrated that engineered CAR-T cells expressing a GPC3 CAR could eliminate GPC3-positive HCC cells [ 141 , 142 , 143 , 144 ]. Therefore, phase I clinical studies designed to evaluate the safety and efficacy of CAR-GPC3 T-cell therapy alone (NCT03980288, NCT04121273, NCT03884751) or in combination with cyclophosphamide and fludarabine (NCT02905188) or other treatment options (NCT04093648, NCT03198546) are currently ongoing and in recruiting status [ 145 , 146 , 147 , 148 , 149 , 150 ].…”
Section: Adoptive Cell Transfer In Hepatocellular Carcinomamentioning
confidence: 99%